(untitled) (Swiss Medical Weekly, 2015)
OBJECTIVE: The number of suicides assisted by right-to-die associations has increased in recent years in Switzerland. The aim of our study was to compare time trends in rates of assisted and unassisted suicide from 1991–2008. METHODS: The Swiss National Cohort is a longitudinal study of mortality in the Swiss population; based on linkage of census data with mortality records up to 2008. The Federal Statistical Office coded suspected assisted suicides from 1998 onwards; and from 2003 onwards right-to-die associations reported the suicides they assisted. We used Poisson regression to analyse trends in rates of suicide per 100’000 person-years, by gender and age groups (15–34, 35–64, 65–94 years). RESULTS: A total of 7’940’297 individuals and 24’842 suicides were included. In women, rates changed little in the younger age groups but increased in 65–94-year-olds, due to an increase in suicide by poisoning (from 5.1 to 17.2 per 100’000; p <0.001). An increase in suicides by poisoning was also observed in older men (from 8.6 to 18.2; p<0.001). Most suicides by poisoning were assisted. In men, suicide rates declined in all age groups, driven by declines in suicide with firearms. CONCLUSIONS: Research is needed to gain a better understanding of the reasons for the tripling of assisted suicide rates in older women, and the doubling of rates in older men, of attitudes and vulnerabilities of those choosing assisted suicide, and of access to palliative care. Rates of assisted suicide should be monitored; including data on patient characteristics and underlying comorbidities.